A confederacy of Dumptys : portraits of American scoundrels in verse - Lithgow, John, 1945- (Chronicle Prism, 2021)
"While the Trump Era was rife with corruption and abuse of power, it was nothing new. Through Lithgow's cutting humor, you will read about a rogues' gallery of villains that came before Donald J. Trump, powerful men and women who were corrupt, venal, criminal, adulterous, racist, or just plain disgusting. With dark and lyrical stories from across American history, you will learn about long-forgotten figures and bad actors of today, including the first Grand Wizard of the Ku Klux Klan, the perpetrator of 19th century women's pyramid schemes, and participants in both the Watergate scandal and the Capitol insurrection. Trump and Nixon show up, of course, but also Leona Helmsley, Boss Tweed, Typhoid Mary, Newt Gingrich, Ted Cruz, and many more. Skipping through time, and delivered with classic Lithgow wit and style, A Confederacy of Dumptys is an exuberant reminder of how not to repeat history"--